Progression of excitation-contraction coupling defects in doxorubicin cardiotoxicity. (January 2019) - Llach, Anna; Mazevet, Marianne; Mateo, Philippe; Villejouvert, Olivier; Ridoux, Audrey; Rucker-Martin, C.; Ribeiro, Maxance; Fischmeister, Rodolphe; Crozatier, Bertrand; Benitah, Jean-Pierre; Morel, Eric; Gómez, Ana M.
Abstract: Cardiac failure is a common complication in cancer survivors treated with anthracyclines. Here we followed up cardiac function and excitation-contraction (EC) coupling in an in vivo doxorubicin (Dox) treated mice model ( iv, total dose of 10 mg/Kg divided once every three days). Cardiac function was evaluated by echocardiography at 2, 6 and 15 weeks after the last injection. While normal at 2 and 6 weeks, ejection fraction was significantly reduced at 15 weeks. In order to evaluate the underlying mechanisms, we measured [Ca 2+ ]i transients by confocal microscopy and action potentials (AP) by patch-clamp technique in cardiomyocytes isolated at these times. Three phases were observed: 1/depression and slowing of the [Ca 2+ ]i transients at 2 weeks after treatment, with occurrence of proarrhythmogenic Ca 2+ waves, 2/compensatory state at 6 weeks, and 3/depression on [Ca 2+ ]i transients and cell contraction at 15 weeks, concomitant with in-vivo defects. These [Ca 2+ ]i transient alterations were observed without cellular hypertrophy or AP prolongation and mirrored the sarcoplasmic reticulum (SR) Ca 2+ load variations. At the molecular level, this was associated with a decrease in the sarcoplasmic reticulum Ca 2+ ATPase (SERCA2a) expression and enhanced RyR2 phosphorylation at the protein kinase A (PKA, pS2808) site (2 and 15 weeks). RyR2 phosphorylation at the Ca 2+ /calmodulin dependent protein kinase II (CaMKII, pS2814) site was enhanced only at 2 weeks, coinciding with the higher incidence of proarrhythmogenic Ca 2+ waves. Our study highlighted, for the first time, the progression of Dox treatment-induced alterations in Ca 2+ handling and identified key components of the underlying Dox cardiotoxicity. These findings should be helpful to understand the early-, intermediate-, and late- cardiotoxicity already recorded in clinic in order to prevent or treat at the subclinical level. Highlights: Anthracyclines anticancer treatment is hampered by their cardiotoxic effects. Doxorubicin injections did not induce mice mortality, but impaired cardiac contractile function 15 weeks later. This cardiac dysfunction could be related to a depressed [Ca 2+ ]i transients 15 weeks after the last injection. Spontaneous Ca 2+ release and enhanced RyR phosphorylation at CaMKII site precedes this depression. Thus alteration in Ca 2+ handling in cardiac myocytes precedes clinical signs of dysfunction.